DESTINTADO EN MEDIO NEUTRO DE PAPEL RECICLADO APLICANDO MEZCLAS DE ENZIMAS CELULASA Y α-AMILASAS - Belkis Sulbarán; José Turrado; Ezequiel Delgado; Orlando Rojas; Richard Venditti (European Scientific Journal, ESJ, 2014)
Deinking of paper recycled is a process which involves the removalof the printed ink pigments, in order to recover clean cellulose fibers suitablefor papermaking (Ferguson, 1992). Deinking is carried out in alkalinemedium, requires the use of chemical reagents. Basically, the deinking canbe divided into two stages: 1) Pulping or disintegration and 2) Deinking and /or washing (Ferguson, 1992; Beneventi and Carré, 2000). Effluentsgenerated in deinking alkaline are unfriendly to the environment, therefore,actually for research have been doing deinking under neutral conditions andnot applying conventional reagents chemical as sodium hydroxide, hydrogenperoxide, sodium silicate, etc. (Jobbins and Heise, 1996; Rosencrance,2007). In deinking under neutral condition only apply surfactants, enzymesor sodium sulfite in substitution of conventional reagents (Bobu and Ciolacu,2008; Alzate et al., 2013). The aims to this study was doing deinking byflotation in neutral condition to apply a mixture of enzyme α-amylase andcellulase (50:50) and compared with a neutral deinking using commercialsurfactants. The data show that the enzyme deinking has better performance85 % of yield, 88 % of brightness and 90 % of removal of residual ink(ERIC) in compared with deinking with surfactants, it has 72 % of yield, 80% brightness and 80% of ERIC.